Opening doors to postgraduate studies: The role of digital technologies and social media - Msimango, S. (South African Journal of Higher Education, 2023)
Regardless of an expansion in enrolments, South Africa continues to encounter a shortage of quality postgraduate output particularly at the Masters and Doctoral levels. Studies have highlighted various explanations behind this shortage. These range from but are not limited to; a poor basic education, pressure from the labour market, curriculum patterns, family and financial responsibilities and a shortage of qualified supervisors. There is a paucity of studies on undergraduate experiences in South Africa and their possible effect on progression to postgraduate studies and knowledge creation in South Africa. The aim of this study was to gain an understanding of the factors that influenced the formation of professional academic identities and factors that made it possible for students to progress to and access postgraduate studies within their chosen fields. To achieve this, qualitative methods were used to collect data from postgraduate students at two universities, and from various faculties. The data was analysed using NVIVO software. It was found that there are many variables that contributed to the development of professional identities and access to postgraduate studies. This article presents two factors which contributed to facilitating access to postgraduate studies which are technology and social media. Taking into consideration South Africa’s higher education context, the funding implications will also be discussed. They form part of a larger model called Tlou Model of Professional Identity Formation, which can be used to help undergraduate students progress to postgraduate.